2022
DOI: 10.1038/s41598-022-11023-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological effects of wound fluid on breast cancer cell lines and human-derived tumor spheroids in 2D and microfluidic culture

Abstract: Intraoperative radiotherapy (IORT) could abrogate cancer recurrences, but the underlying mechanisms are unclear. To clarify the effects of IORT-induced wound fluid on tumor progression, we treated breast cancer cell lines and human-derived tumor spheroids in 2D and microfluidic cell culture systems, respectively. The viability, migration, and invasion of the cells under treatment of IORT-induced wound fluid (WF-RT) and the cells under surgery-induced wound fluid (WF) were compared. Our findings showed that cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 88 publications
1
3
0
Order By: Relevance
“…IORT-seroma-treated and non-IORT-seroma-treated cells showed no significant change in expression levels of proteins associated with cell cycle arrest (P16, P21) and the expression level of Caspase 3. Furthermore, our results confirmed the previous findings about tumor progressive effects of seroma on these three BC cell lines ( 124 ). Figure 5 presents the studies related to the effects of seroma on BC cell lines.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…IORT-seroma-treated and non-IORT-seroma-treated cells showed no significant change in expression levels of proteins associated with cell cycle arrest (P16, P21) and the expression level of Caspase 3. Furthermore, our results confirmed the previous findings about tumor progressive effects of seroma on these three BC cell lines ( 124 ). Figure 5 presents the studies related to the effects of seroma on BC cell lines.…”
Section: Introductionsupporting
confidence: 92%
“…It is worth noting that in both IORT-seroma and non-IORT-seroma groups, the expression levels of both E-cadherin and Caspase 3 were significantly higher in seroma-treated spheroids compared to RPMI-treated spheroids (as control). This study suggested IORT-seroma as a fluid containing inhibitory factors for tumor migration in the microfluidic system ( 124 ). Also, we showed increased proliferative and migrative characteristics of spheroids from four BC patients under IORT-seroma treatment using time-lapse imaging ( 127 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The staining process proceeded with incubation of cells with the dyes for 45 min at 37 ◦ C in the tissue culture incubator and then visualized under a fluorescence microscope. [ 48b,95 ]…”
Section: Methodsmentioning
confidence: 99%